Biomedical Applications of Nano-Sized Polymeric Micelles and Polyion Complexes - Alexander Kabanov (Журнал Сибирского федерального университета: Серия Биология, 2018)
The paper provides a high-level overview of the use of polymeric micelles, polyion complexes, cell mediated drug carriers and exosomes in the therapy of cancer and neurodegenerative diseases. The author tries to combine the lessons-learned during over a quarter of century work in the field of nanomedicine and drug delivery along with a vision statement of some trends and future prospective in this field. Several most recent examples from the University of North Carolina and Moscow State University laboratories are presented including high capacity polymeric micelles for single and multiple water-insoluble drugs for cancer therapy. The nanoscale size polyion complexes formed by ionic block copolymers and polypeptides for the delivery of these polypeptides are also discussed. Examples include antioxidant enzymes (e.g. superoxide dismutase, catalase), stoichiometric and catalytic scavengers of organophosphorus toxins (butirylcholine esterase, organophosphate hydrolase) and neurotrophins (brain-derived neurotrophic factor, glial cell line-derived neurotrophic factor). The applications include treatments of obesity, stroke, Parkinson’s disease, RETT syndrome, organophosphorus toxins poisoning, and some other medical conditions that have been demonstrated using animal models. The application of these complexes in the context of the macrophage carriers for drug delivery to the site of inflammation is presented. A concept of the use of genetically modified macrophages as natural gene delivery vectors is stated and illustrated using Parkinson’s disease therapy as an example. The role of exosomes in gene and protein delivery and its potential as a true pharmaceutical modality are also discussed